Regulation of Appetite and Satiety by Gastrointestinal Peptides - Sarah H. Mhaibes; Najwan K. Fakree; Sonia I. Naser (College of Pharmacy University of Baghdad, 2021)
In recent decades, global obesity has increased significantly, causing a major health problem with associated complications and major socioeconomic issues. The central nervous system (CNS), particularly the hypothalamus, regulates food intake through sensing the metabolic signals of peripheral organs and modulating feeding behaviors.  The hypothalamus interacts with other brain regions such as the brain stem to perform these vital functions. The gut plays a crucial role in controlling food consumption and energy homeostasis. The gut releases orexigenic and anorexigenic hormones that interact directly with the CNS or indirectly through vagal afferent neurons. Gastrointestinal peptides (GIP) including cholecystokinin, peptide YY, Nesfatin-1, glucagon-like peptide 1, and oxyntomodulin send satiety signals to the brain and ghrelin transmit hunger signals to the brain. The GIP is essential for the control of food consumption; thus, explain the link between the gastrointestinal tract (GIT) and the brain is important for managing obesity and its associated diseases. This review aimed to explain the role of gut peptides in satiety and hunger control.